2021
DOI: 10.28940/terra.v39i0.833
|View full text |Cite
|
Sign up to set email alerts
|

Aplicación de ácidos húmicos, quitosano y hongos micorrízicos como influyen en el crecimiento y desarrollo de pimiento

Abstract: La aplicación de biofertilizantes y bioestimulantes influyen en varias respuestas fisiológicas de los cultivos, con ello se puede potencializar la calidad de las cosechas. Por lo cual la utilización de dichos productos puede minimizar la fertilización sintética, al mismo tiempo de incrementar la tolerancia al estrés biótico en el agroecosistema. Este estudio fue desarrollado con el propósito de valorar el impacto del quitosano, hongos micorrízicos y ácidos húmicos en el crecimiento de variedades de pimiento en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
1
0
2
Order By: Relevance
“…The results obtained agree with those reported by the authors of [16], who tested whether humic acids applied to the substrate (15 g/kg of substrate) positively influenced the growth of coffee seedlings. Likewise, it coincides with reports in other crops: cucumber [17], carrot [18], pepper [19], and [20], which used humic substances and directly influenced the growth of coffee crops, specifically the height of the coffee plant.…”
Section: A Biometric Growth Parameters: Plant Height Number Of Leaves...supporting
confidence: 89%
“…The results obtained agree with those reported by the authors of [16], who tested whether humic acids applied to the substrate (15 g/kg of substrate) positively influenced the growth of coffee seedlings. Likewise, it coincides with reports in other crops: cucumber [17], carrot [18], pepper [19], and [20], which used humic substances and directly influenced the growth of coffee crops, specifically the height of the coffee plant.…”
Section: A Biometric Growth Parameters: Plant Height Number Of Leaves...supporting
confidence: 89%
“…In addition, the application of this biopolymer also promotes plant growth; in potato, it is reported that it stimulates stomatal closure and reduces the effects of abiotic stress. In chili bell pepper plants, it stimulates germination, seedling emergence, and increases height, stem diameter, biomass and yield compared to controls [45]. Similarly, Reyes-Perez et al [46] mentioned that in tomatoes, germination, development and production increased due to the fact that chitosan increases photosynthesis and chlorophyll production, helps in stomatal closure, which makes water use more efficient, and its decomposition can produce ammonium, which is used by the plant.…”
Section: Discussionmentioning
confidence: 98%
“…En este contexto, la industria química busca soluciones más ecológicas y económicas en donde los biofertilizantes han surgido como una opción prometedora. Estos, también llamados fertilizantes orgánicos, son productos compuestos a partir de organismos vivos, como las tan difundidas lombrices californianas (Cardona et al, 2021), o de microorganismos como los hongos micorrízicos (Reyes-Pérez et al, 2021) con propiedades benéficas que mejoran las características biológicas del suelo, aumentando la productividad de los cultivos y mejorando la calidad de los productos; asimismo, presentan bajos niveles de contaminación ambiental y representan una opción rentable para los agricultores (Collahuazo y Araujo, 2019). Una posible fuente para la producción de biofertilizantes son las microalgas, que ya han sido estudiadas como biofertilizantes o bioestimulantes para diferentes cultivos (Coppens et al, 2016;Ronga et al, 2019;Das et al, 2019).…”
Section: Introductionunclassified